2016
DOI: 10.2503/hortj.mi-073
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of N Derived from a Hairy Vetch Incorporated in the Previous Year to Tomato N Uptake under Hairy Vetch-tomato Rotational Cropping System

Abstract: Utilization of cover crops helps the establishment of environmentally friendly agriculture due to their nutrition supplying ability mainly in the current year of application, but cover crop-derived N also remains until the following year. In the present study, the nutritional effect of a cover crop on tomato production in a greenhouse in the following year was investigated using the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Chemical N fertilizer may build up soil organic N, because 10% to 50% of N applied to the soil is immobilized by microbes within the first year after fertilization (Mulvaney et al, 2009;Shen et al, 1989). Increased soil N stock in the HV and HV + compost treatments would be expected because HV and compost residue effects on the soil N pool may last for a long time (Eghball et al, 2004;Sugihara et al, 2016;Wallingford et al, 1975). However, under openfield conditions, the effectiveness of HV in increasing the soil N pool may depend on the amount of residue added to the soil (Kuo et al, 1997b), soil temperature, and soil moisture.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical N fertilizer may build up soil organic N, because 10% to 50% of N applied to the soil is immobilized by microbes within the first year after fertilization (Mulvaney et al, 2009;Shen et al, 1989). Increased soil N stock in the HV and HV + compost treatments would be expected because HV and compost residue effects on the soil N pool may last for a long time (Eghball et al, 2004;Sugihara et al, 2016;Wallingford et al, 1975). However, under openfield conditions, the effectiveness of HV in increasing the soil N pool may depend on the amount of residue added to the soil (Kuo et al, 1997b), soil temperature, and soil moisture.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern suggests that although much of its N was released in the first 4-6 weeks after application, the N release continued for long period due to decomposition of residues that were initially resistant to microbial degradation (Hue and Silva, 2000). In this regard, Sugihara et al (2016) reported that HV applied in the previous year contributed slightly to the tomato growth when planted in the following year, especially in the early growth stages. The increased SIN in the first weeks after residue incorporation may indicate that HV is suitable to be used as a nitrogen source for the early growth stages of tomatoes.…”
Section: Soil Carbon and Nitrogenmentioning
confidence: 99%
“…In recent years, the interaction between rhizosphere organisms has become the subject of increasing amounts of researches [ 21 ]. The rotation of tomato with xerophytes or rice have been assessed by many studies [ 22 24 ], but there are few studies on rotation with aquatic vegetables. Arrowhead ( Sagittaria sagittifolia ) is an exceptional aquatic vegetable in the Lixiahe region, which is rich in starch, protein, vitamins and other nutrients [ 25 ].…”
Section: Introductionmentioning
confidence: 99%